The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s10853-011-5347-5
|View full text |Cite
|
Sign up to set email alerts
|

TEM investigation on zirconate formation and chromium poisoning in LSM/YSZ cathode

Abstract: Cell durability is a crucial technological issue for SOFC commercialization, and considerable progress has been made

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 30 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…The degradation in the current density for both cases is due to the increase in the polarization resistance, , corresponding to the increasingly enlarged Nyquist arcs over time (Figure a,b). The degradation mechanism is inferred from the Bode plots in Figure a,b, given that the impedance at low (≤30 Hz) and high (≤3 kHz) frequencies are responses to the transfer of O 2– ions along the surface and across the bulk, respectively. , The electrode performance degradation by Cr poisoning is due to the preferential Cr deposition at the triple phase boundary (TPB) between air, electrode, and electrolyte via the following electrochemical reduction. In contrast, the degradation by S poisoning is due to the chemisorption of SO 2 on the LSM surface, resulting in SrSO 4 precipitation and nonstoichiometric, Sr-depleted LSM. ,, …”
Section: Resultsmentioning
confidence: 99%
“…The degradation in the current density for both cases is due to the increase in the polarization resistance, , corresponding to the increasingly enlarged Nyquist arcs over time (Figure a,b). The degradation mechanism is inferred from the Bode plots in Figure a,b, given that the impedance at low (≤30 Hz) and high (≤3 kHz) frequencies are responses to the transfer of O 2– ions along the surface and across the bulk, respectively. , The electrode performance degradation by Cr poisoning is due to the preferential Cr deposition at the triple phase boundary (TPB) between air, electrode, and electrolyte via the following electrochemical reduction. In contrast, the degradation by S poisoning is due to the chemisorption of SO 2 on the LSM surface, resulting in SrSO 4 precipitation and nonstoichiometric, Sr-depleted LSM. ,, …”
Section: Resultsmentioning
confidence: 99%
“…In another study by the authors, 36 Si was identified in TEM investigations at LSM/YSZ and zirconate/LSM interfaces, where Si was possibly combined with Zr and/or La as a silicate phase. As these phases were only sparsely observed within other TEM samples from this same repeat-element and as their formation is more likely linked to the reaction of endogenous Si with cathode material during sintering, the here-observed glass-forming exogenous Si contamination is suggested to have significantly contributed to cathode degradation.…”
Section: Resultsmentioning
confidence: 92%
“…The reactive trapping of volatile Cr species within the LSC CCL, as previously reported in (17), is suggested to lower the Cr concentration on the cathode surface decreasing both the Cr amounts at the interface and their distribution in the cathode thickness. Regarding the nature of the Cr accumulations, analyses of composition and phase identification is already reported elsewhere (18) and beyond the scope of the present work.…”
Section: Cr Profilingmentioning
confidence: 95%